Management of childhood cataract: practice patterns among ophthalmologists in Nigeria (2023)
OBJECTIVE: To describe the practice patterns for the management of paediatric cataracts among ophthalmologists practising in Nigeria. METHODS: A cross-sectional study of fully trained Nigerian ophthalmologists who perform cataract surgery in children aged 16 years and below. An online questionnaire was distributed via e-mail and social media platforms to respondents. Data on socio-demographic characteristics, type, location and years of practice, status and preferred approach to management of childhood cataracts were obtained and analysed. RESULTS: =A total of 41 ophthalmologists responded that they perform paediatric cataract surgery. Of these, 25 (61.0%) were paediatric ophthalmologists while 7(17.0%) were general ophthalmologists. Most respondents (92.7%) practise in urban settings and 30(73.2%) work in tertiary hospitals. Most respondents (90.2%) routinely insert intracular lenses (IOLs) in children aged 2 years and above while 32(78.0%) routinely under-correct the IOL power. Thirty-four (82.9%) have an anterior vitrectomy machine, 31 (75.6%) routinely perform posterior capsulotomy and anterior vitrectomy, and 17 (58.5%) routinely perform same-day sequential bilateral cataract surgery. Twenty-six respondents (63.4%) respondents routinely give near correction in aphakic children, while 24 (58.5%) respondents routinely give bifocals in pseudophakic children. Compared to other sub-specialists, paediatric opthalmologists were 24 times more likely to routinely under-correct IOL power (p=0.001) and 4 times more likely to routinely correct near vision in aphakic children (0.036) as well as prescribe bifocals for pseudophakic children respectively (0.029). CONCLUSION: The practice of paediatric cataract surgery in Nigeria is mainly in line with expected standards, but there is a need for the development of detailed practice guidelines.